2010
DOI: 10.1051/parasite/2010172113
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial community associated with the leechMyzobdella lugubrisLeidy 1851 (Hirudinea: Piscicolidae) from Lake Erie, Michigan, USA

Abstract: Summary:Leeches are widespread in the Great Lakes Basin, yet their potential to harbor disease-causing agents has not been investigated. The purpose of this study was to identify the bacterial community of the commonly occurring leech, Myzobdella lugubris, within the Lake Erie Watershed. Leech samples were collected from the pectoral fins of channel catfish, Ictalurus punctatus, and freshwater drum, Aplodinotus grunniens, from Lake Erie in commercial trap nets and pooled into two samples based on host attachme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The tissue damage caused by this leech compromises the integrity of bass buccal mucosa and allows for potential invasion by pathogenic bacteria and viruses. In this context, recent studies from the authors’ laboratory have demonstrated that M. lugubris carries the Viral Hemorrhagic Septicemia Virus (Faisal & Schulz, 2009), a disease that has devastated important fish stocks in the Laurentian Great Lakes; and Flavobacterium psychrophilum , the causative agent of both Bacterial Coldwater Disease and Rainbow Trout Fry Syndrome, which can cause high mortalities in salmonids (Schulz & Faisal, 2010). Other species of leeches are well known for functioning as vehicles for transmission of infectious agents in fish (Dombrowski, 1952; Ahne, 1985; Cusack & Cone, 1986; Kruse et al ., 1989; Jones & Woo, 1992; Zintl et al ., 2000; Kikuchi et al ., 2002; Hemmingsen et al ., 2005; Kikuchi & Fukatsu, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The tissue damage caused by this leech compromises the integrity of bass buccal mucosa and allows for potential invasion by pathogenic bacteria and viruses. In this context, recent studies from the authors’ laboratory have demonstrated that M. lugubris carries the Viral Hemorrhagic Septicemia Virus (Faisal & Schulz, 2009), a disease that has devastated important fish stocks in the Laurentian Great Lakes; and Flavobacterium psychrophilum , the causative agent of both Bacterial Coldwater Disease and Rainbow Trout Fry Syndrome, which can cause high mortalities in salmonids (Schulz & Faisal, 2010). Other species of leeches are well known for functioning as vehicles for transmission of infectious agents in fish (Dombrowski, 1952; Ahne, 1985; Cusack & Cone, 1986; Kruse et al ., 1989; Jones & Woo, 1992; Zintl et al ., 2000; Kikuchi et al ., 2002; Hemmingsen et al ., 2005; Kikuchi & Fukatsu, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…al, 1975). M. lugubris attachment points may become superficially infected (Faisal et al., 2011; Noga et al., 1990; Pomposini et al., 2019) and can facilitate pathogen entry, potentially including viral haemorrhagic septicaemia virus (VHSV) in the Laurentian Great Lakes (Faisal & Schulz, 2009; Schulz & Faisal, 2010; Schulz et al., 2011). In the oral cavity, detachment of M. lugubris results in circular mucosal depressions (MD).…”
Section: Introductionmentioning
confidence: 99%
“…Leeches feeding on the blood of numerous aquatic animals such as fishes, amphibians, water birds and mammals (including humans) are a source of pathogens for successive hosts. Additionally various microorganisms living in the natural water reservoir can colonize the leeches (Eroglu et al, 2001;Schulz and Faisal, 2010). More than 650 species of leech have been identified, but only 15 of them are used medically and are classified as medicinal leeches.…”
Section: Introductionmentioning
confidence: 99%